2018
DOI: 10.1002/bjs5.50119
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of therapeutic nipple‐sparingversusskin‐sparing mastectomy

Abstract: Background The use of nipple‐sparing mastectomy (NSM) is increasing, despite unproven oncological safety in the therapeutic setting. The aim of this systematic review was to determine the safety and efficacy of NSM compared with skin‐sparing mastectomy (SSM). Methods A literature search of all original studies including RCTs, cohort studies and case–control studies comparing women undergoing therapeutic NSM or SSM for breast cancer was undertaken. Primary outcomes were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
42
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(52 citation statements)
references
References 50 publications
3
42
0
2
Order By: Relevance
“…62 In their 2018 systematic review comparing 1,419 NSMs to 1,596 SSMs, Agha et al also reported no statistical difference between these procedures with regard to both mortality and local recurrence. 63 In a retrospective 2019 study, with a mean follow-up time of 62 months, investigating patients who underwent therapeutic NSM followed by immediate reconstruction, 59 patients (tumor-to-nipple distance of < 2.0 cm) were compared with 134 patients (tumor-to-nipple distance of > 2.0 cm). 64 There were no significant differences found between these groups with respect to ER, PR, HER2-neu status, or nodal involvement.…”
Section: Oncologic Outcomesmentioning
confidence: 99%
“…62 In their 2018 systematic review comparing 1,419 NSMs to 1,596 SSMs, Agha et al also reported no statistical difference between these procedures with regard to both mortality and local recurrence. 63 In a retrospective 2019 study, with a mean follow-up time of 62 months, investigating patients who underwent therapeutic NSM followed by immediate reconstruction, 59 patients (tumor-to-nipple distance of < 2.0 cm) were compared with 134 patients (tumor-to-nipple distance of > 2.0 cm). 64 There were no significant differences found between these groups with respect to ER, PR, HER2-neu status, or nodal involvement.…”
Section: Oncologic Outcomesmentioning
confidence: 99%
“…Meta-analysis has shown that it is oncologically safe to preserve the nipple during mastectomy. 8 For aesthetic reasons Nipple sparing mastectomy has become the operation of choice both in the risk reduction setting and in cancer cases where surgeon is confident to get a clear margin. However, nipple sparing mastectomy has resulted in increased complications mainly due to nipple necrosis as shown in the systematic review.…”
Section: Discussionmentioning
confidence: 99%
“…However, nipple sparing mastectomy has resulted in increased complications mainly due to nipple necrosis as shown in the systematic review. 8 This could be due to operations involving incisions around the nipple and mastectomy flap which may compromise the blood supply leading to increased ischemic complications. This may also be the case in nipple sacrificing mastectomy where you excise the nipple during mastectomy.…”
Section: Discussionmentioning
confidence: 99%
“…However, rolling up the expanded skin for tissue supplementation to create a breast mound may raise concerns about oncologic safety. However, there is no need to worry about cancer recurrence in the skin that remains post-mastectomy, as the oncologic safety of nipple-areolar skin-sparing mastectomy has been proven and widely accepted [13][14][15]. If a general surgeon performs mastectomy and confirms that the resection margins are free of cancer, this technique may be considered safe on the basis of the evidence to date.…”
Section: Discussionmentioning
confidence: 99%